Lactobacillus casei Zhang exerts probiotic effects to antibiotic-treated rats - Guoqiang Yao (Elsevier, 2021)
Probiotics administration can facilitate the restoration of host gut microbiota/metabolome after antibiotic treatment. Yet, the mechanism behind such beneficial effects remains unclear. This study constructed a rat model of antibiotic-induced gut dysbiosis to monitor the effects and mechanism of probiotic (Lactobacillus casei Zhang) treatment in maintaining gut homeostasis and restoring the gut microbiota/metabolome. Forty rats were randomly divided into four groups (n = 10 per group): control receiving only saline (Ctrl), antibiotic (AB-Ctrl), antibiotic followed by probiotic (AB-Prob), and antibiotic plus probiotic followed by probiotic (AB + Prob). Rat fecal microbiota and sera were collected at four time points from pre-treatment to post-treatment. The probiotic-treated group (AB + Prob) had significantly more Parabacteroides (P.) goldsteinii after one week of antibiotic and probiotic intervention but fewer antibiotic resistance genes (ARGs)-possessing bacteria (Clostridioides difficile and Burkholderiales bacterium). Consistently, metabolomics data revealed that both probiotic groups had more acetic acid, propionic acid, butyric acid, and valeric acid post treatment. Moreover, a potential probiotic species, P. goldsteinii, strongly correlated with L. casei, as well as propionic acid, butyric acid, and valeric acid. Furthermore, administering probiotic lowered the serum IL-1α level. In contrast, the antibiotic-recipients had a higher irreversible level of IL-1α, suggesting inflammation of the rats. Thus, antibiotic treatment not only led to host gut dysbiosis, but inflammatory responses and an increase in gut ARGs. Daily L. casei Zhang supplementation could alleviate the side effect of cefdinir intervention and facilitate the restoration of gut microbial homeostasis, and these probiotic effects might involve P. goldsteinii-mediated beneficial activities.